Apnea-Hypopnea Index in Chronic Obstructive Pulmonary Disease Exacerbation Requiring Noninvasive Mechanical Ventilation with Average Volume-Assured Pressure Support. (27th November 2021) - Briones-Claudett, Killen H.; Romero Lopez, Adela; Briones-Claudett, Mónica H.; Cabrera Baños, Mariuxi del Pilar; Briones Zamora, Killen H.; Briones Marquez, Diana C.; Icaza-Freire, Andrea P.; Zimmermann, Luc J. I.; Gavilanes, Antonio W. D.; Grunauer, Michelle
Abstract : Introduction . This study intends to determine the Apnea-Hypopnea Index in patients hospitalized with acute hypercapnic respiratory failure from chronic obstructive pulmonary disease exacerbation, who require noninvasive ventilation with average volume-assured pressure support (AVAPS), as well as describes the clinical characteristics of these patients. Materials and Methods . We designed a single-center prospective study. The coexistence of Apnea-Hypopnea Index and clinical, gasometric, spirometric, respiratory polygraphy, and ventilatory characteristics were determined. The clinical characteristics found were categorized and compared according to the Apnea-Hypopnea Index (AHI) < 5, AHI 5–15, and AHI >15. A p value <0.05 was considered statistically significant. Results . During the study period, a total of 100 patients were admitted to the ICU with a diagnosis of acute hypercapnic respiratory failure due to COPD exacerbation. 72 patients presented with acute respiratory failure and fulfilled criteria for ventilatory support. Within them, 24 received invasive mechanical ventilation and 48 NIV. After applying the inclusion criteria for this study, 30 patients were eligible. An AHI >5 was present in 24 of the 30 patients recruited (80%). Neck circumference (cm), Epworth scale, and Mallampati score evidenced significant differences when compared to the patient's AHI <5, AHI 5–15, and AHI >15 (p < 0.05 ). Furthermore, patients with an AHI >5 had longer hospital admissions, prolonged periods on mechanical ventilation, and a higher percentage of intubation rates. Conclusion . Apnea-Hypopnea Index and chronic obstructive pulmonary disease exacerbation are a frequent association found in patients with acute hypercapnic respiratory failure and COPD exacerbations that require NIV. This association could be a determining factor in the response to NIV, especially when AVAPS is used as a ventilatory strategy.